1992
DOI: 10.1084/jem.176.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Epstein-Barr virus cytotoxic T cell epitopes using recombinant vaccinia: implications for vaccine development.

Abstract: Summal~There is considerable interest in designing an effective vaccine to the ubiquitous Epstein-Barr virus (EBV). An important role for EBV-specific cytotoxic T lymphocytes (CTLs) in eliminating virus-infected cells is well established. Limited studies using a small number of immune donors have defined target epitopes within the latent antigens of EBV. The present study provides an extensive analysis of the distribution of class I-restricted CTL epitopes within EBV-encoded proteins. Using recombinant vaccini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
233
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(237 citation statements)
references
References 27 publications
4
233
0
Order By: Relevance
“…Human fetal thymic cells (containing 1  10 7 thymocytes, thymocytes: thymic epithelial cells and other stromal cells  1 : 1; immature and mature NKT cells were positively depleted) (17,18) were transplanted into thymi of anaesthetised SCID mice. The chimaeras were then intrathymically challenged with EBV (10 7 pfu) (14,21). The challenge was repeated once after 6 days.…”
Section: Human-thymus-scid Chimaeras and Humanised Xenogeneic Tumour-mentioning
confidence: 99%
“…Human fetal thymic cells (containing 1  10 7 thymocytes, thymocytes: thymic epithelial cells and other stromal cells  1 : 1; immature and mature NKT cells were positively depleted) (17,18) were transplanted into thymi of anaesthetised SCID mice. The chimaeras were then intrathymically challenged with EBV (10 7 pfu) (14,21). The challenge was repeated once after 6 days.…”
Section: Human-thymus-scid Chimaeras and Humanised Xenogeneic Tumour-mentioning
confidence: 99%
“…Although blocking experiments were not undertaken in all patients investigated, the data obtained showed the same characteristics for the EBV-specific CTL response as reported for healthy individuals. [13][14][15] It can be substantially blocked by antibodies directed against CD3 or CD8, while anti-CD4 or anti-MHC class II show no effect, and the main effector cells are CD8-positive CTLs. MHC class I restriction is further underlined by experiments using EBNA-derived nonapeptides presented by autologous PHA blasts, which demonstrated that the EBV-directed CTLs recognize only the peptide known to be associated with HLA-B8 (therefore matching the patients HLA-haplotype), whereas another, HLA-A11-restricted EBV-peptide did not lead to a significant lysis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 This surveillance is based mainly on CD8-positive HLA-restricted memory T cells found in the peripheral blood of seropositive individuals which can be reactivated in vitro by challenge with autologous EBVinfected B cells. [13][14][15][16][17] In immunosuppressed individuals, reactivation of this latent EBV infection can lead to the outgrowth of EBV-transformed B lymphocytes with unregulated polyclonal or monoclonal lymphoproliferation, of which the latter has a rapidly progressive and uniformly fatal course. 18,19 For this reason, the EBV-directed CTL response has been carefully investigated after allogeneic BMT, where up to 30% of the recipients of allografts from mismatched or matched unrelated donors may develop EBV lymphoma.…”
mentioning
confidence: 99%
“…45 The observation that the GAr does not inhibit priming of CTL is important and consistent with reports describing the presence of EBNA-1-specific CTL in EBV-seropositive individuals. [31][32][33][34][35][36] As antigen presentation by professional APC, most likely DC, is crucial to the initiation of virusspecific CTL responses, the presence of EBNA-1-specific CTL in EBV-positive donors suggests that antigen processing for MHC class I by specialized APC is not hampered by the GAr. In case EBV-specific CTL are induced through the direct route following EBV infection of DC, these observations would indicate that antigen presentation in DC differs intrinsically from presentation by 'nonprofessional' APC.…”
Section: Discussionmentioning
confidence: 99%
“…Although EBNA-1-specific CTL have been described in infectious mononucleosis patients and healthy carriers, they cannot recognize EBV-infected cells. [31][32][33][34][35][36] The failure to recognize endogenously expressed EBNA-1 has been attributed to the glycine-alanine repeat (GAr) domain in the EBNA-1 sequence that protects EBNA-1 from proteasomal degradation and subsequent presentation in the context of MHC class I. 37,38 This successful immune-evasion strategy points to the unique opportunity to hide cells expressing transgenes from CTLmediated target-cell destruction by incorporation of the GAr sequence into the transgene.…”
Section: Introductionmentioning
confidence: 99%